Performance evaluation and improvement strategy for FTP servers in campus network - Wei LIU; Gang LI; Feng YU (Tongxin xuebao)
FTP is one of the important application systems in campus network.But most FTP servers have bottleneck in their performances,which causes low utilization to the resource.Therefore,according to the actual demand of the network in high schools,the working principle of existing FTP softwares was analyzed.The node number and processing rate of servers were further studied.Then based on multithreading principle,the queue theory models of FTP servers were put forward.By the analysis of bandwidth utilization,response time and processing rate of the nodes,corresponding improved schemes were also proposed.